KAJIAN KARAKTERISTIK SENSORIS, FISIK, DAN KIMIA FRUIT LEATHER ISANG TANDUK (Musa corniculata Lour.) DENGAN PENAMBAHAN BERBAGAI KONSENTRASI GUM ARAB - Astuti, Tri; Widowati, Esti; Atmaka, Windi (Universitas Sebelas Maret (UNS), 2015)
Fruit leather is one of the processed fruit products, shaped similar to thin sheets with specific consistency and flavor. One of the suitable fruits that can be processed to fruit leather was horn plantain (Musa corniculata Lour.). The aim of this research was to determine the effect of the addition of gum arabic on sensoryand physical, and chemical characteristics of horn plantain fruit leather and most acceptable gum arabic concentration addition for consumer. The analysis method used was Completely Randomized Design (CRD) with single factor of the addition of gum arabic. Concentration addition of gum arabic in horn plantain fruit leatherwas 0,3%; 0,6%; and 0,9%. Based on the analysis result according to the sensory analysis using hedonic test, the addition of gum arabic to the horn plantain fruit leather resulted a significant effect on the parameters of color, texture, and overall, whereas the addition of gum arabic to the horn plantain fruit leather did not have a significant effect on the parameters of scent and flavor. The physical and chemical analysis result of the horn plantain fruit leather with gum arabic addition had significant effect on water content (12,696% -13,775% (wb)) and dietary fiber (2,7563% - 5,0825% (db)), and had no significant effect on ash content (2,875% - 2,896% (db)), water activity (Aw) (0,54 - 0,56), and tensile strength (4,8449 N - 5,8125 N). The recommended gum arabic addition to the horn plaintain fruit leather was 0,6%.Keywords: arabic gum, fruit leather, horn plantain